The Effectiveness of Iot Use on Supply Chain Management Under Extreme Conditions in The Copper Cleaner Project - Nyoman Oka Wahyudhi; Bambang Endro Yuwono; Darmawan Pontan; Inavonna Inavonna (Eduvest - Journal of Universal Studies, 2025)
The success of a project cannot be separated from a series of activities that include planning, implementation and supervision stages. In Time control on a project, it is very necessary for a project to be able to complete the project on time or earlier than planned. The time control method used in this study is the Supply Chain Collaboration, Integration and Relations method. This research was conducted on the PT XYZ Mining Facility Development Project, Mimika Regency, Papua which aims to find out the project performance and get solutions to the problems that occur in the mining facility construction project. The data used in this study are Time Schedule, Construction Plan, Worker Supply Plan and weekly progress report. The implementation of IoT technology in logistics processes significantly improves the efficiency and effectiveness of the supply chain. In the copper cleaner project, the application of IoT was able to reduce delivery delays by an average of 13% and increase the reliability rate of delivery (on-time delivery) to 85%.